Optimization and Control of Electrical Machines (IntechOpen, 2023)
Electrical machines are used in the process of energy conversion in the generation, transmission and consumption of electric power. In addition to this, electrical machines are considered the main part of electrical drive systems. Electrical machines are the subject of advanced research. In the development of an electrical machine, the design of its different structures is very important. This design ensures the robustness, energy efficiency, optimal cost and high reliability of the system. Using advanced techniques of control and new technology products has brought electrical machines into their optimal functioning mode. Different techniques of control can be applied depending on the goals considered. The aim of this book is to present recent work on the design, control and applications of electrical machines.